SOSIALISASI MENGENAI POTENSI PRODUK BIOTEKNOLOGI FARMASI BERUPA FORMULASI DAN SEDIAAN SPRAY KOMBUCHA BUNGA TELANG DAN BIOTEKNOLOGI PERTANIAN BERUPA PUPUK CAIR ORGANIK DARI LIMBAH FERMENTASI KOMBUCHA BUNGA TELANG KEPADA PETANI HORTIKULTURA K.P PEKUNCEN - Rezaldi, Firman; Utami, Arti Wahyu; Sari, Sinta Wisma; Faizah, Nai’matul Retno; Wati, Dyah Rohma; Resti Wijayanti, Fitria Eka; Ginaris, Rifkarosita Putri; Purbanova, Reni; Sugiono, Sugiono; Saifullah, Ipul; Rohmatulloh, Rizal; Kurniawan, Maskun; Munir, Misbakhul; Mu'jijah, Mu'jijah; Sasmita, Heny; Somantri, Ucu Wandi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Abdurachman Saleh Situbondo, 2024)
Horticultural commodity crops are commodities that have high selling value and have properties as functional food and pharmaceutical ingredients. So the majority of horticultural farmers often prioritize meeting market needs. Obstacles that occur in the field are decreasing quality and quantity due to pest and disease attacks as well as excessive use of chemical-based fertilizers. The aim that can be offered in this community service activity is to provide education about the potential of butterfly pea flower kombucha, apart from being used as a functional food, it can also be used as a natural antibiotic without other additives as an antifungal pathogen from horticultural commodity plants as well as providing education about the potential of butterfly pea flower kombucha as a raw material for organic liquid fertilizer to support the growth of horticultural commodity plants which has been proven by various research results. by providing an explanation of the basics of butterfly pea flower kombucha fermentation which is useful as a probiotic drink to enhance the immune system in general which has a high potential for being a functional food, pharmaceutical/medicinal or cosmetic, an ingredient in organic liquid fertilizer preparations, and a natural antibiotic for fungal pathogens of horticultural plants. Horticultural farmers from Pekuncen village learned about the potential of butterfly pea flower kombucha with a percentage of 100% after the presentation of the material.